The role of the military within Official Development Assistance : policies, parameters and procedures : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Bennett, Vernon Noel (Massey University, 2009)
This thesis explores the relationship between development, Official Development Assistance (ODA) and the military in order to determine both the nature and effects of that relationship, and how the involvement of the military within ODA can be conducted in the most appropriate manner to support development. This study was conducted with regard to the current links between security and development within international relations and concerns that ODA is being drawn from a primarily development role to one that more explicitly supports national foreign and security policy ends instead. This issue is explored by defining development, ODA and the military as separate variables and then employing a grounded theory approach to develop an understanding of the relationship between them. The results of the study show that the involvement of the military within ODA and development may occur throughout the full range of operational contexts in which the military may be employed and can encompass activities throughout the scope of the functions of development. This involvement can in turn create a range of positive and negative impacts upon the conduct of ODA and development as the military serves to moderate the direction and strength of the relationship between the two. From this, the role of the military within ODA is identified as potentially an enabling, implementing and coordinating agency – primarily during times of crisis and conflict. The study then relates this role back to the wider context through considering the management of the military’s role and identifying the policies, parameters and procedures that may help to ensure that this role is conducted in the most appropriate manner for development.
Keywords: Official Development Assistance; ODA; Civil-military relations; Humanitarian assistance; Foreign policy; Role of military; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360204 Defence studies